TRAINING OF INSTRUCTORS OF THE AVIATION EDUCATIONAL INSTITUTIONS AT THE NATIONAL AVIATION UNIVERSITY - Smolinchuk, Larysa; Alpatova, Oleksandra; Lytvynchuk, Nataliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article deals with the peculiarities of training of instructors of the aviation educational institutions at the National Aviation University. The purpose of training instructors is the formation of professional competencies within the existing qualifications, necessary for professional activity as a teacher. This activity has its own specifics and requires thorough psychological and pedagogical training. Study Conduct. The Department of Pedagogy and Psychology of Occupational Education carried out the study to improve the training of instructors as well as to take into account the experience of organizing relevant training. The survey of teachers (5 teachers with more than 20 years of work experience) and students (76 people) was conducted, regarding the structure, content of the program, the sequence of studying topics, methods and technologies of education. Results. At the National Aviation University, the training of instructors of aviation educational institutions is carried out according to the improved program “Instructor (teacher) of an aviation educational institution”. The proposed program includes five main content blocks, which allows the instructors to develop competencies aimed at organizing and conducting professional training of aviation personnel in accordance with the established requirements. Conclusions. Training and retraining programs for aviation specialists need constant updating, taking into account the modern industry achievements. This, in turn, confirms the need for continuous improvement of the training of instructors (teachers) of aviation educational institutions. In order to improve the quality of professional training and implement the regulatory instructions and recommendations set forth in the documents regulating activities in the field of aviation, the professional training of instructors must be organized in accordance with the requirements of the Air Code of Ukraine and ICAO and be based on modern psychological and pedagogical research